Findings of magnetic resonance and neurological outcome in newborns with Hypoxic Ischemic En-cephalopathy: integrative review (Research, Society and Development, 2021)
The aim of the study was to analyze the main findings in neuroimaging exams and neurodevelopmental outcomes in children with hypoxic-ischemic encephalopathy. This is an integrative review in which searches were performed on the CINAHL and PubMed databases, with the following inclusion criteria: cohort studies, clinical trials, publications from the last 5 years in the languages of Portuguese, English and Spanish. Infant: birth-23 months, Infant: 1-23 months, human, diagnosis by magnetic resonance, tomography and electroencephalogram. Of the 2,248 articles that were identified, 11 were selected to compose the study. Imaging tests showed the prevalence of lesions in the basal ganglia and thalamus and in white matter. The main neurological results identified were characterized as motor, cognitive and language delay. There was a higher frequency of lesions in Basal Ganglia, Thalamus and in the White Matter was discovered by means of magnetic resonance imaging. Regarding child development, the main outcomes identified were motor, cognitive and language delay. This study points out the disadvantages caused by the limited access to neuroimaging techniques in developing countries, as well as the lack of standardized instruments for assessing child development.